THE USE OF DOUBLE MATCH PICTURE MEDIA FOR TEACHING READING COMPREHENSION - Diyah Dwi Agustina (Premise: Journal of English Education and Applied Linguistics, 2018)
This Classroom Action Research is intended to improve the students’ reading comprehension mastery and learning motivation of the eight grade SMPN 1 Purbolinggo. The participant of the research is  the class VIIIA of SMPN 1 Purbolinggo, East Lampung. They consisted of 30 students. This research uses Kemmis and Taggart’s model; planning, action, observation and reflection of the result. Meanwhile, this research employs the triangulation method (observation, interview, and test) to collect the data. After the data are gathered, they are analyzed and interpreted by using data reduction, categorization and synthesis. The findings were formulated as follow: (1) the implementation used more varieties media in presenting the materials using double match picture. Most of the students become more active in learning process; (2) the improvement of students’ reading comprehension could be seen from the test, the mean score improved from 68 in cycle 1 become 73 in cycle 2. Then, in cycle 3 the score is 81 or all of the students pass the minimum passing grade; (3) there is improvement in the students learning motivation and interest. It could be seen from the observation result, questionnaire and interview. After the implementation, most of the students become interested and motivated in reading during teaching and learning process.